Work order for groove cutting, finishing, dismantling lab floor tiles, re-plastering or install for Brac University new campus project - Brac University (Brac University, 2023)
This work order has been made between Brac University and Sanjib Goldeer for groove cutting, finishing, dismantling lab floor tiles, re-plastering or install for Brac University new campus project.